Internalisasi nilai-nilai Islam dalam Pendidikan Formal dan Informal: kajian literatur tentang akidah, syariah, dan akhlak - Parhan, Muhamad; Diana Dwi Pratiwi; Firna Sabila Diria; Hilma Aulia; Naresta Putri Karimah (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
The rapid development of technology has significantly influencing the Islamic identity of the younger generation. One of the consequences is the weakening of students' character, indicating that religious values, particularly in the aspects of aqidah (belief), shari'ah (law), and akhlaq (ethics), still need to be instilled and reinforced. This study aims to examine the efforts to internalize Islamic values in the areas of aqidah, shari'ah, and akhlaq in both formal and informal educational settings. This research employs a literature review method, analyzing previous studies related to the importance of internalizing Islamic values through both types of education. The findings indicate that the internalization of Islamic values—comprising aqidah, shari'ah, and akhlaq—plays a crucial role in shaping the character of students. This process of internalization should begin early through informal education and continue in formal education from childhood to adulthood. The consistent embedding of Islamic values significantly influences the development of a person's character and personality and contributes to the creation of a society that upholds strong Islamic values. he internalization of Islamic values is essential to develop a generation that is not only academically knowledgeable but also ethically upright.